EVALUASI KINERJA PEMASOK DENGAN METODE ANALYTICHIERARCHY PROCESS - Zahir, Saktiva Moryza (Operations Excellence: Journal of Applied Industrial Engineering, 2016)
Abstract. This study aims to determine the performance assessment criteria for suppliers with better criteria based on previous research and the study of literature, also measure the performance of suppliers using the criteria. The research data is the data performance per supplier during the period January to August 2013. The sampling method used is a saturated sampling where the entire population is taken as a sample with a population of 9 people and 3 people for a sample of experts. The analytical method used in this study is the Analytical Hierarchy Process (AHP). The results showed that the criteria can be used in the company and of the simulation shown significant results from suppliers that serve as sample simulations. The criteria are include quality and durability testing, delivery, price, responsiveness, financial stability and business, information development process, technical ability and a good & stable background. After done supplier performance assessment using criteria that already selected resulting effective measurement, example using 3 company supplier which is generating a decision for best supplier selection that can cooperate with company positively. Assessment can be done for improving supplier performance with purpose improving performance based on worse criteria that supplier has. Keywords: Supplier Performance Assessment, AHP, Analytical Hierarchy Process, Supplier Performance Effective Measurement, Supplier Selection & Decision